Synthesis of Zinc Oxide Nanoparticles by Ecofriendly Routes: Adsorbent for Copper Removal From Wastewater - Primo, Julia de O.; Bittencourt, Carla; Acosta, Selene; Sierra-Castillo, Ayrton; Colomer, Jean-François; Jaerger, Silvia; Teixeira, Verônica C.; Anaissi, Fauze J. (Frontiers in Chemistry, 2020)
Zinc Oxide nanoparticles have been synthesized by two simple routes using Aloe vera (green synthesis, route I) or Cassava Starch (gelatinization, route II). The XRD patterns and Raman spectra show that both synthesis routes lead to single-phase ZnO. XPS results indicate the presence of zinc atoms with oxidation state Zn2+. SEM images of the ZnO nanoparticles synthesized using Starch show the presence of pseudo-spherical nanoparticles and nanosheets, while just pseudo-spherical nanoparticles were observed when Aloe vera was used. The UV-Vis spectra showed a slight difference in the absorption edge of the ZnO particles obtained using Aloe vera (3.18 eV) and Starch (3.24 eV). The ZnO nanoparticles were tested as adsorbents for the removal of copper in wastewater, it is shown that at low Cu2+ ion concentration (⁓40 mg/L) the nanoparticles synthesized by both routes have the same removal efficiency, however, increasing the absorbate concentration (> 80 mg / L) the ZnO nanoparticles synthesized using Aloe vera have a greater removal efficiency. The synthesized ZnO nanoparticles can be used as effective and environment friendly metal trace absorbers in wastewater.